Analysis of Mapping Forest, Settlement, and Rice Field Areas in Konawe Selatan District, Indonesia - Andri Estining Sejati; I Gede Purwana Edi Saputra (Geosfera Indonesia, 2021)
The rampant land-use change in Konawe Selatan District and the uncontrolled use leads to disaster and environmental stability effect, consequently, mapping the area function is important for controlling land-use activities to reduce the risk of disaster. Therefore, this study aims to determine the direction, distribution, and effective area of the function of forests, settlements, and rice fields. This study used a regional survey with a quantitative approach. Base map data of administrative, slope class, soil type, rainfall, and land-use obtained from the regional planning agency and SAS Planet were used and analyzed with quantitative descriptive analysis overlayed with scoring. The result showed that the direction of area functions was dominated by limited production forests by 50.05% while the distribution of protected forest function was spread across 14 sub-districts with limited production forests in all sub-districts, production forests in 17 sub-districts, settlements in 21 sub-districts, and rice fields in 9 sub-districts. Furthermore, the effective area shows that all area functions are accordance with the directions, except for rice fields which took over the function of forest while the effective area controlled by the regional planning shows that all area functions need correction following the regulation of the Minister of Agriculture of Indonesia. Areas which do not accordance with the function need to be evaluated, hence, regional planning is required to be revised by the people's representative in Konawe Selatan. Keywords: Analysis; Forest; Rice field; Settlement; Mapping Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License